Discovery of novel chloropyramine-cinnamic acid hybrids as potential FAK inhibitors for intervention of metastatic triple-negative breast cancer. (15th July 2022) - Yang, Fei; Xu, Kangping; Zhang, Sha; Zhang, Jinlin; Qiu, Yaoren; Luo, Jin; Tan, Guishan; Zou, Zhenxing; Wang, Wenxuan; Kang, Fenghua
Graphical abstract: Highlights: 7d exhibited low micromolar antiproliferative activity against TNBC cells but sparing non-tumor breast cells. 7d significantly inhibited both invasion and migration of MDA-MB-231 cells. 7d strongly suppressed the Y925 autophosphorylation of FAK, formation of FAs and SFs of TNBC cells as well as induced apoptosis of MDA-MB-231 cells. Abstract: To search for novel focal adhesion kinase (FAK) inhibitors for intervention of metastatic triple-negative breast cancer (TNBC), a series of hybrids 7a -s from chloropyramine and cinnamic acid analogs were designed, synthesized and biologically evaluated. The most active compound 7d could potently inhibit the proliferation, invasion and migration of TNBC cells in vitro. The docking analysis of 7d was performed to elucidate its possible binding modes to focal adhesion targeting (FAT) domain of FAK scaffold. Further mechanism studies indicated the ability of 7d in disrupting Y925 autophosphorylation of FAK, reducing formation of focal adhesions (FAs) and stress fibers (SFs) as well as inducing apoptosis of TNBC cells. Together, 7d is a novel FAK inhibitor to inhibit the essential nonkinase scaffolding function of FAK via binding FAT domain and may be worth studying further for intervention of TNBC.